2021
DOI: 10.3389/fpls.2021.718092
|View full text |Cite
|
Sign up to set email alerts
|

Production of Feminized Seeds of High CBD Cannabis sativa L. by Manipulation of Sex Expression and Its Application to Breeding

Abstract: The use of the cannabis plant as a source of therapeutic compounds is gaining great importance since restrictions on its growth and use are gradually reduced throughout the world. Intensification of medical (drug type) cannabis production stimulated breeding activities aimed at developing new, improved cultivars with precisely defined, and stable cannabinoid profiles. The effects of several exogenous substances, known to be involved in sex expressions, such as silver thiosulfate (STS), gibberellic acid (GA), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 38 publications
3
36
1
Order By: Relevance
“…Lubell et al [14] treated four cultivars of female hemp with 0.3 and 3 mM STS solution and reported 100% conversion to male flowers at 3 mM concentration. Differences in the number of flowers between STS and GA3 were observed by Flajšman et al [30], who reported 379 total male flowers with 20 mM STS and below 25 male flowers treated with 0.01% GA3 on two CBD-rich breeding populations. In our study, the number of male flowers produced between 21 and 24 DAF were similar for both solutions; however, TPC determined by IFC (Figure 2) showed that STS produced a significantly higher amount of pollen compared to GA3 at all sampling dates.…”
Section: Source Of Variationmentioning
confidence: 83%
See 1 more Smart Citation
“…Lubell et al [14] treated four cultivars of female hemp with 0.3 and 3 mM STS solution and reported 100% conversion to male flowers at 3 mM concentration. Differences in the number of flowers between STS and GA3 were observed by Flajšman et al [30], who reported 379 total male flowers with 20 mM STS and below 25 male flowers treated with 0.01% GA3 on two CBD-rich breeding populations. In our study, the number of male flowers produced between 21 and 24 DAF were similar for both solutions; however, TPC determined by IFC (Figure 2) showed that STS produced a significantly higher amount of pollen compared to GA3 at all sampling dates.…”
Section: Source Of Variationmentioning
confidence: 83%
“…The results of this study confirmed the observation of Ram et al [12], Rosenthal [13], and Green [33], as male flowers were produced for both genotypes, KAN and A4, by applying STS and GA3. In previous studies [12,14,30], the quantity of pollen was not considered while defining the efficiency of treatment to induced masculinity in female plants of cannabis. Our results reported that TPC were significantly different between two treatments at all sampling dates, while the difference in the number of flowers per plant was not significant between solutions and genotypes between 21 and 24 DAF (Figure 1a).…”
Section: Effect Of Chemical Solution On Tpc At Various Sampling Datesmentioning
confidence: 99%
“…The obtained progenies were selected for morphological and growth uniformity within each population and for high CBD content at the industrial production level. Only genetically female plants were cultivated, which were crossed and propagated with feminised seeds obtained by manipulating sex expression, as reported in our recent publication (Flajšman et al, 2021). This approach enabled us to develop two feminised high CBD breeding populations of medical cannabis, one corresponding to the "narrow leaflet drug type" (named MX-CBD-11) and the other one to the "wide leaflet drug type" (named MX-CBD-707) phenotype based on plant morphology according to McPartland (2017McPartland ( , 2018.…”
Section: Methodsmentioning
confidence: 99%
“…This pre-legalization exploratory work identified silver-containing compounds such as silver thiosulfate (STS), a potent inhibitor of ethylene signalling, as promoting the production of male flowers on female plants (induced male flowers; IMF) and aqueous ethephon ((2-Chloroethyl) phosphonic acid), which rapidly decomposes to produce ethylene gas, as promoting the production of female flowers on male plants (induced female flowers; IFF) as shown in Figure 1. Following the legalization of cannabis in some jurisdictions, the inverse effects of STS and ethephon on cannabis sex have been re-demonstrated, quantified and published by a handful of research groups (Lubell & Brand, 2018;Kurtz et al, 2020;Moon et al, 2020a;Flajšman et al, 2021), pointing to ethylene as being an effector of sexual plasticity. Although the phenotypic outcomes of these treatments in cannabis have been quantified, to date there are no studies which have sought to understand the underlying molecular mechanisms controlling ethylene-related sexual plasticity in cannabis.…”
Section: Introductionmentioning
confidence: 99%